Affective responses by adults with autism are reduced to social images but elevated to images related to circumscribed interests. - Noah J Sasson; Gabriel S Dichter; James W Bodfish (PLoS ONE, 2012)
Individuals with autism spectrum disorders (ASD) demonstrate increased visual attention and elevated brain reward circuitry responses to images related to circumscribed interests (CI), suggesting that a heightened affective response to CI may underlie their disproportionate salience and reward value in ASD. To determine if individuals with ASD differ from typically developing (TD) adults in their subjective emotional experience of CI object images, non-CI object images and social images, 213 TD adults and 56 adults with ASD provided arousal ratings (sensation of being energized varying along a dimension from calm to excited) and valence ratings (emotionality varying along dimension of approach to withdrawal) for a series of 114 images derived from previous research on CI. The groups did not differ on arousal ratings for any image type, but ASD adults provided higher valence ratings than TD adults for CI-related images, and lower valence ratings for social images. Even after co-varying the effects of sex, the ASD group, but not the TD group, gave higher valence ratings to CI images than social images. These findings provide additional evidence that ASD is characterized by a preference for certain categories of non-social objects and a reduced preference for social stimuli, and support the dissemination of this image set for examining aspects of the circumscribed interest phenotype in ASD.